2019
DOI: 10.1186/s40635-019-0244-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sweep gas flow on extracorporeal CO2 removal (ECCO2R)

Abstract: BackgroundVeno-venous extracorporeal carbon dioxide (CO2) removal (vv-ECCO2R) is increasingly being used in the setting of acute respiratory failure. Blood flow rates range in clinical practice from 200 mL/min to more than 1500 mL/min, and sweep gas flow rates range from less than 1 to more than 10 L/min. The present porcine model study was aimed at determining the impact of varying sweep gas flow rates on CO2 removal under different blood flow conditions and membrane lung surface areas.MethodsTwo different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The amount of CO 2 removed is higher for a blood flow of approximately 0.4 L/minute and a membrane surface areas of 0.59 m 2 than has been reported in previous studies, including those where membranes with larger surface areas were explored. [28][29][30] Furthermore, the amount of CO 2 removed also varies with the blood flow -for any given sweep flow, a higher blood flow results in a greater CO 2 clearance. 28 It is likely that this is due to the far higher PCO 2 in patients' venous blood than in the in vitro models as it is known that the PCO 2 and total CO 2 content in venous blood are important determinants of the CO 2 which can be removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of CO 2 removed is higher for a blood flow of approximately 0.4 L/minute and a membrane surface areas of 0.59 m 2 than has been reported in previous studies, including those where membranes with larger surface areas were explored. [28][29][30] Furthermore, the amount of CO 2 removed also varies with the blood flow -for any given sweep flow, a higher blood flow results in a greater CO 2 clearance. 28 It is likely that this is due to the far higher PCO 2 in patients' venous blood than in the in vitro models as it is known that the PCO 2 and total CO 2 content in venous blood are important determinants of the CO 2 which can be removed.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Furthermore, the amount of CO 2 removed also varies with the blood flow -for any given sweep flow, a higher blood flow results in a greater CO 2 clearance. 28 It is likely that this is due to the far higher PCO 2 in patients' venous blood than in the in vitro models as it is known that the PCO 2 and total CO 2 content in venous blood are important determinants of the CO 2 which can be removed. 29 Indeed, when the inlet PCO 2 is normalized, the VCO 2 is reduced, although the relationship between CO 2 clearance and sweep gas flow is maintained (Figure 1(b)).…”
Section: Discussionmentioning
confidence: 99%
“…In daily clinical practice, systems operating at blood flow rates up to 500 mL/min remove CO 2 on the order of 80 mL/min. This can be nearly doubled by doubling the blood flow rate, thereby accounting for approximately 50% of the CO 2 production of an adult resting intensive care unit (ICU) patient [1922]. Furthermore, ECMO therapy for neonatal and pediatric patients uses comparable blood flow rates with current rotary blood pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Animal data conflict with one another. Karagiannidis et al [ 11 , 12 ] demonstrated, using a porcine model, that a blood flow rate > 1 L/min with a membrane lung with a surface area > 0.8 m 2 may remove the 50% of total CO 2 production and correct severe respiratory acidosis. Contrarily, Duscio et al [ 10 ] reported a very high VCO 2 (171 mL/min) with a low blood flow (400 mL/min) and a high surface membrane lung (1.8 m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal data, instead, were controversial. Duscio et al [ 10 ] reported very high CO 2 removal (171 mL/min) using a low-flow device (400 mL/min), while Karagiannidis et al [ 11 , 12 ] showed that only high blood flow rates (>900 mL/min) and adequate membrane lungs (surface area > 1 m 2 ) can effectively correct severe respiratory acidosis. However, both studies converge on the point that the sweep gas flow can increase CO 2 removal only when high blood flow rates are used.…”
Section: Introductionmentioning
confidence: 99%